2014
DOI: 10.15376/biores.9.4.6166-6192
|View full text |Cite
|
Sign up to set email alerts
|

Microcrystalline Cellulose from Plant Wastes through Sodium Hydroxide-Anthraquinone-Ethanol Pulping

Abstract: Microcrystalline cellulose was prepared from wastes of Tithonia diversifolia, inflorescence stems of Musa sapientum, and Musa paradisiaca by soda-anthraquinone-ethanol pulping method. They were bleached by sodium chlorite and then alpha-cellulose was isolated, followed by preparation of microcrystalline cellulose. The study revealed the effect of various processing stages on the properties of the cellulose obtained. Yields of more than 80% of microcrystalline cellulose were obtained. Fourier transform infrared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 60 publications
2
16
1
Order By: Relevance
“…Accordingly, the poor flowability behaviors are obvious from the Hausner's ratio and Carr's index results. The flowability results obtained for BH-MCC were not unusual, as other authors had reported similar values for different MCC (Ejikeme, 2008;Bhimte and Tayade, 2007;Ohwoavworhua and Adelakun, 2005;Oluwasina et al, 2014).…”
Section: Crystallinitysupporting
confidence: 73%
“…Accordingly, the poor flowability behaviors are obvious from the Hausner's ratio and Carr's index results. The flowability results obtained for BH-MCC were not unusual, as other authors had reported similar values for different MCC (Ejikeme, 2008;Bhimte and Tayade, 2007;Ohwoavworhua and Adelakun, 2005;Oluwasina et al, 2014).…”
Section: Crystallinitysupporting
confidence: 73%
“…The high resolution XPS spectra of 5 display peaks at 101.8 eV corresponding to (Fig. 3 c) 36 ; 710.26 eV and 723.85 eV corresponding to and of and (Fig. 3 d) 37 , 38 .…”
Section: Resultsmentioning
confidence: 99%
“…The equatorial proton of the anhydroglucose unit of starch (Oluwasina et al . ) (δ 5.2–5.4 ppm) was considered to be the internal standard. The extent of OSA substitution was determined by integration of the methyl protons of the OSA (δ 0.8–0.9 ppm).…”
Section: Methodsmentioning
confidence: 99%